Comparing a knowledge‐based 3D reconstruction algorithm to TomTec 3D echocardiogram algorithm in measuring left cardiac chamber volumes in the pediatric population. - Ahmad, Attila; Shigemitsu, Sachie; Termachi, Yozo; Windram, Jonathan; Khoo, Nee; Colen, Tim; Eckersley, Luke (Echocardiography, 2022)
Background: Three‐dimensional echocardiography (3DE) is an emerging method for volumetric cardiac measurements; however, few vendor‐neutral analysis packages exist. Ventripoint Medical System Plus (VMS3.0+) proprietary software utilizes a validated Magnetic resonance imaging (MRI) database of normal ventricular and atrial morphologies to calculate chamber volumes. This study aimed to compare left ventricular (LV) and atrial (LA) volumes obtained using VMS3.0+ to Tomtec echocardiography analysis software. Methods: Healthy controls (n = 98) aged 0–18 years were prospectively recruited and 3D DICOM datasets focused on the LV and LA acquired. LV and LA volumes and ejection fractions were measured using TomTec Image Arena 3D LV analysis package and using VMS3.0+. Pearson correlation coefficients, Bland–Altman's plots, and intraclass coefficients (ICC) were calculated, along with analysis time. Results: There was a very good correlation between Ventripoint Medical System (VMS) and Tomtec LV systolic (r2 =.88, ICC.89 [95% CI.81,.94]), and diastolic (r2 =.88, ICC.90 [95% CI.77,.95]) volumes, and between VMS and Tomtec LA diastolic (r2 =.75, ICC.89 [95% CI.81,.93]) and systolic (r2 =.88, ICC.91 [95% CI.78,.96]) volumes on linear regression models. Natural log transformations eliminated heteroscedasticity, and power transformations provided the best fit. The time (mins) to analyze volumes using VMS were less than using Tomtec (LV VMS 2.3 ±.5, Tomtec 3.3 ±.8, p <.001; LA: VMS 1.9 ±.4, Tomtec 3.4 ± 1.0, p <.001). Conclusions: There was a very good correlation between knowledge‐based (VMS3.0+) and 3D (Tomtec) algorithms when measuring 3D echocardiography‐derived LA and LV volumes in pediatric patients. VMS was slightly faster than Tomtec in analyzing volumetric measurements.